AKT regulates NPM dependent ARF localization and p53(mut) stability in tumors - Hamilton, Garth (Impact Journals LLC, 2014)
Nucleophosmin (NPM) is known to regulate ARF subcellular localization and MDM2 activity in response to oncogenic stress, though the precise mechanism has remained elusive. Here we describe how NPM and ARF associate in the nucleoplasm to form a MDM2 inhibitory complex. We find that oligomerization of NPM drives nucleolar accumulation of ARF. Moreover, the formation of NPM and ARF oligomers antagonizes MDM2 association with the inhibitory complex, leading to activation of MDM2 E3-ligase activity and targeting of p53. We find that AKT phosphorylation of NPM-Ser48 prevents oligomerization that results in nucleoplasmic localization of ARF, constitutive MDM2 inhibition and stabilization of p53. We also show that ARF promotes p53 mutant stability in tumors and suppresses p73 mediated p21 expression and senescence. We demonstrate that AKT and PI3K inhibitors may be effective in treatment of therapeutically resistant tumors with elevated AKT and carrying gain of function mutations in p53. Our results show that the clinical candidate AKT inhibitor MK-2206 promotes ARF nucleolar localization, reduced p53(mut) stability and increased sensitivity to ionizing radiation in a xenograft model of pancreatic cancer. Analysis of human tumors indicates that phospho-S48-NPM may be a useful biomarker for monitoring AKT activity and in vivo efficacy of AKT inhibitor treatment. Critically, we propose that combination therapy involving PI3K-AKT inhibitors would benefit from a patient stratification rationale based on ARF and p53(mut) status.